Potential of Antibacterial Producing Rhizosphere Bacteria from Porang Roots (Amorphophallus muelleri Blume) against Gastrointestinal Pathogens - Nuryanti, Siska; Nurung, Ayyub Harly; Akihito mr, Andi Al Kahfi (Journal Microbiology Science, 2025)
Increasing antibiotic resistance in gastrointestinal pathogens such as Escherichia coli, Shigella dysenteriae, and Vibrio cholerae encourages the search for new antimicrobial agents. This study aims to evaluate the antibacterial potential of rhizosphere bacteria from porang roots (Amorphophallus muelleri Blume) against the three pathogens through in vitro tests. Isolation was carried out from rhizosphere soil using a serial dilution technique. Eleven isolates were characterized morphologically and tested for antibacterial activity using the agar diffusion method. Two selected isolates (IBRAM-2 and IBRAM-11) were fermented and extracted with ethyl acetate. Antibacterial activity was evaluated using the Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC) tests with the microdilution and drop plate methods, each with three replications and chloramphenicol as a positive control. The results showed an inhibition zone of 13.2–18.7 mm. The MIC value is 25,000 ppm, while the MBC value ranges from 25,000–50,000 ppm. Although it shows antibacterial activity, the high concentration required indicates weak antibacterial potential.